2023
DOI: 10.1136/bmjgh-2022-011253
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and perinatal mortality in the urban continuum: a geospatial analysis of the household survey, satellite imagery and travel time data in Tanzania

Abstract: IntroductionRecent studies suggest that the urban advantage of lower neonatal mortality in urban compared with rural areas may be reversing, but methodological challenges include misclassification of neonatal deaths and stillbirths, and oversimplification of the variation in urban environments. We address these challenges and assess the association between urban residence and neonatal/perinatal mortality in Tanzania.MethodsThe Tanzania Demographic and Health Survey (DHS) 2015–2016 was used to assess birth outc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The study found that illness recognition pathways were not significantly different among clusters, with healthcare professionals and traditional birth attendants being the primary sources of initial recognition [39]. These findings are very different from previously reported pathways in other LMICs using the same VASA tool [6,28,40]. However, care-seeking patterns differed between high-and lowmortality clusters, with a higher proportion of cases perceiving care was not needed in high mortality clusters [41].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The study found that illness recognition pathways were not significantly different among clusters, with healthcare professionals and traditional birth attendants being the primary sources of initial recognition [39]. These findings are very different from previously reported pathways in other LMICs using the same VASA tool [6,28,40]. However, care-seeking patterns differed between high-and lowmortality clusters, with a higher proportion of cases perceiving care was not needed in high mortality clusters [41].…”
Section: Discussioncontrasting
confidence: 68%
“…Most of these deaths could have been prevented with better healthcare and interventions [3,4]. However, burden remain in high in most disadvantaged in urban slums and rural areas, where poverty, inadequate sanitation, and limited access to healthcare increase the risk of these event [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is happening at a time when the use of health facilities for childbirth is near universal (>90%) 3 in African urban conurbations (a city area containing many people, formed by various towns growing and merging ( https://dictionary.cambridge.org/dictionary/english/conurbation )). Yet, emerging evidence shows that the odds of maternal death and stillbirth are significantly higher in urban areas compared to rural areas 25 27 . Consequently, spatial accessibility to EmOC in African urban settings has never been more crucial if we are to avert maternal and stillbirths and reach the 2030 Sustainable Development Goals (SDG) 28 on maternal and newborn deaths.…”
Section: Background and Summarymentioning
confidence: 99%
“…Urban residence is associated with mortality rates for adults, children under 5 and newborns, [4][5][6][7] all of which are used as proxy measures of population health. Additionally, urbanisation influences other health outcomes, such as disease burden, immunisation rates and the provision and use of reproductive and maternal healthcare, including childbirth care and associated quality.…”
Section: Bmj Global Healthmentioning
confidence: 99%